High flux and antifouling properties of negatively charged membrane for dyeing wastewater treatment by membrane distillation. (15th October 2016) - An, Alicia Kyoungjin; Guo, Jiaxin; Jeong, Sanghyun; Lee, Eui-Jong; Tabatabai, S. Assiyeh Alizadeh; Leiknes, TorOve
Abstract: This study investigated the applicability of membrane distillation (MD) to treat dyeing wastewater discharged by the textile industry. Four different dyes containing methylene blue (MB), crystal violet (CV), acid red 18 (AR18), and acid yellow 36 (AY36) were tested. Two types of hydrophobic membranes made of polytetrafluoroethylene (PTFE) and polyvinylidene fluoride (PVDF) were used. The membranes were characterized by testing against each dye (foulant-foulant) and the membrane–dye (membrane-foulant) interfacial interactions and their mechanisms were identified. The MD membranes possessed negative charges, which facilitated the treatment of acid and azo dyes of the same charge and showed higher fluxes. In addition, PTFE membrane reduced the wettability with higher hydrophobicity of the membrane surface. The PTFE membrane evidenced especially its resistant to dye absorption, as its strong negative charge and chemical structure caused a flake-like (loose) dye–dye structure to form on the membrane surface rather than in the membrane pores. This also enabled the recovery of flux and membrane properties by water flushing (WF), thereby direct-contact MD with PTFE membrane treating 100 mg/L of dye mixtures showed stable flux and superior color removal during five days operation. Thus, MD shows a potential for stable long-term operation in conjunction with a simple membrane cleaning process, and its suitability in dyeing wastewater treatment. Graphical abstract: Highlights: Direct contact membrane distillation (DCMD) was tested with different dye solutions. MD showed a high potential for treating of dyeing wastewater. The high membrane porosity and hydrophobicity lead to high flux and low fouling. Negatively charged dyes showed a low fouling on negative zeta potential MD membranes. Water flushing enabled a long-term application of DCMD by removing dye foulant.